Khazanah aswaja : memahami, mengamalkan dan mendakwahkan Ahlussunnah wal Jamaah - Khazanah_aswaja_:_memahami,_mengamalkan_dan_mendakwahkan_Ahlussunnah_wal_Jamaah (Aswaja NU Center PWNU, 2016)
st,3./ws.c.1-3